A syntrophic co-fermentation model for bio-hydrogen production. (1st October 2021) - Wang, Yi; Jing, Yanyan; Lu, Chaoyang; Kongjan, Prawit; Wang, Jian; Awasthi, Mukesh Kumar; Tahir, Nadeem; Zhang, Quanguo
Abstract: Bio-hydrogen production based on lignocellulosic biomass provide clean and neutral route for bio-fuels production with promising prospective. In this work, we used a hydrogen-producing enriched consortium and explored a syntrophic co-fermentation model to evaluate microbial community evolution and carbon transfer route of co-fermentation system with lignocellulosic biomass for hydrogen production. Maximum hydrogen production levels of 165.4 mL/g with mean hydrogen concentrations of 52.3% were recorded. Community evolution analysis revealed that the main contributor to hydrogen production was photosynthetic bacterium with about 70% contribution. Anaerobic bacteria were involved in lignocellulosic degradation and carbon transfer processes. In addition, some non-hydrogen producing microbes perform beneficial effects of metabolic adjustment by consuming accumulative organic acids to maintain stable hydrogen production. This study shows that the syntrophic co-fermentation system has the potential for clean energy production with sustainable supply prospective. Graphical abstract: Image 1 Highlights: A syntrophic cofermentation model for bio-hydrogen production was explored. Abundant microbial community support the high rate of hydrogen production. The predominant microorganisms exhibit stable abundance and play a key role in hydrogen production. Community evolution help to release organic acid stress and enhance hydrogen production.